Bimetallic ag-au nanoparticles inside mesoporous titania thin films: Synthesis by photoreduction and galvanic replacement, and catalytic activity - Coneo Rodríguez, Rusbel (2020)
In this work, the synthesis and catalytic activity of bimetallic Ag–Au nanoparticles (NPs) supported in TiO2 mesoporous thin films (MTFs) are presented. The composite materials were obtained through a two-step procedure, performed at room conditions. In the first step, Ag NPs were grown inside the MTFs by photoreduction. Then, a galvanic replacement reaction with Au was carried out, yielding the bimetallic NPs. The composites were characterized by UV/Vis spectroscopy, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and X-ray reflectometry (XRR), which show that the alloyed Ag–Au NPs are present inside the mesopores. Moreover, Ag and Au composition relationship can be controlled by adjusting the reaction times of the photoreduction and galvanic replacement reactions, respectively. Pores remain accessible after NPs synthesis, a feature that ensures their possible applications in any device that requires the contact between the NPs and the medium. Catalytic activity of the composites towards 4-nitrophenol reduction by sodium borohydride was evaluated. Although all the bimetallic systems exhibit improved catalytic properties in comparison with the monometallic Ag composite, the sample with lower Au/Ag relationship is the most effective. For the first time, to the best of our knowledge, bimetallic Au–Ag NPs are encapsulated inside mesoporous TiO2 films, paving the way towards a wide variety of applications.